Halloysite nanotube and its firing products: Structural characterization of halloysite, metahalloysite, spinel type silicoaluminate and mullite - Andrini, Leandro Ruben (2019)
Halloysite and its heating products demand attention due to its multiple technological applications, and in particular for its natural nanostructure. The purpose of this paper is to present a structural characterization of these materials and its firing products up to mullite. To achieve this objective, the techniques of conventional X-ray diffraction (XRD) and X-ray absorption near-edge structure (XANES) were used, in addition to scanning electron microscopy (SEM), and simultaneous thermogravimetric and differential thermal analysis (DTA-TG). SEM has allowed to prove that the nanotubular morphology (acicular) of halloysite was retained for all temperatures (500, 800, 1100 and 1250 °C). For the temperatures between 500 and 800 °C the metahalloysite phase was identified. The 1100 °C fired samples presented the spinel aluminosilicate phase. Finally, after high temperature treatments the mullite phase was detected as the only aluminum containing crystalline phase accompanied by cristobalite and glassy phase. The XANES spectra confirmed the octahedral aluminum coordination in native halloysite, this coordination was progressively lost with the thermal treatments giving place to the presence of the four folded coordination. In the intermediate treatments, the so called metahalloysite phase, presented some three and five coordination slight contributions. Particularly, the metahalloysite Al K XANES spectra were not reported before.